Analisis Pedagogi Kritis Dan Asas Kepastian Hukum Atas Surat Edaran Gubernur DIY Nomor 29/SE/V/2021 Tentang Memperdengarkan Lagu Kebangsaan Indonesia Raya - Hani Subagio; Hastangka Hastangka; Danang Prasetyo (Jayapangus Press, 2023)
This research analyzes the principle of legal certainty on the Circular Letter of Yogyakarta Special Region (DIY) Governor Number 29/SE/V/2021 about playing the Indonesia Raya national anthem. Since the issuance of the letter, there have been polemics about the content of the Circular Letter of DIY Governor which are considered to have the potential to be materially and immaterially detrimental if it is going to be implemented. Other polemics arise about the urgency and the content material substance in the Circular Letter of DIY Governor which are potentially contradicting other laws. Even though the Circular Letter is a product of policy, not a product of law, it is juridically impacting institutions under the policymaker. The method used of this research is the normative law research approach. The primary data are the Circular Letter of DIY Governor Number 29/SE/V/2021, Law Number 24/2009 about the national flag, language, symbol, and anthem. Meanwhile, the secondary data are books and research result that are relevant to the topic. The data analysis is conducted by using positive law content and structural analysis. The result of the research shows that the Circular Letter of DIY governor has content material that has the potential to be inconsistent with the content material of article 59 UU Number 24/2009. In addition, the format of the letter does not meet the prevailing terms. In general, the content material of the Circular Letter of DIY Governor may occur of legal uncertainty in the implementation. In addition, in the perspective of critical pedagogy, forcing a national education together with community activities will lead to resistance and apathy.